The cicadas (Hemiptera: Cicadidae) of Suriname including the description of two new species, five new combinations, and three new records - Sanborn, Allen F. (Zootaxa, 2020)
The known cicada fauna of Suriname is identified. Zammara guyanensis n. sp., and Proarna proximorubrovenosa n. sp. are described as new. The taxa Zammara eximia Erichson, 1848, Cicada thalassina Germar, 1830, Cicadetta surinamensis (Kirkaldy, 1909), Cicada collaris Degeer, 1773 and Cicada melanoptera Gmelin, 1789 (=Cicada marginata Degeer, 1773) are reassigned to become Zammaralna eximia (Erichson, 1848) n. comb., Hyantia thalassina (Germar, 1830) n. comb., Taphura surinamensis (Kirkaldy, 1909) n. comb., Alocha collaris (Degeer, 1773) n. comb. (Cicadellidae: Cicadellinae: Cicadellini), and Homalodisca melaoptera (Gmelin, 1789) n. comb. (Cicadellidae: Cicadellinae: Proconiini), respectively. The first records of Fidicina christinae Boulard & Martinelli, 1996, Guyalna bicolor (Olivier, 1790), and Majeorona truncata Goding, 1925 are provided. Included are the first Suriname records for the genera Guyalna Boulard & Martinelli, 1996, Majeorona Distant, 1905c, and Hyantia Stål, 1866. The taxon Neotibicen tibicen tibicen (Linnaeus, 1758) is removed from the fauna of Suriname with references to this taxon considered misidentifications of Fidicina mannifera (Fabricius, 1803). Cicada collaris Degeer, 1773, and Cicada melanoptera Gmelin, 1789 (=Cicada marginata Degeer, 1773) are reassigned to the Cicadellidae and also removed from the cicada faunal list. The currently known cicada fauna of Suriname is comprised of 15 species from nine genera, three tribes and two subfamilies. The known cicada fauna diversity is increased 50% with this work.